Occurrence of Textile Dyes and Metals in Tunisian Textile Dyeing Effluent: Effects on Oxidative Stress Status and Histological Changes in Balb/c Mice - Methneni, Nosra; Ezdini, Khawla; Ben Abdeljelil, Nouha; Van Loco, Joris; Van den Houwe, Kathy; Jabeur, Riheb; Fekih Sallem, Ons; Jaziri, Ahlem; Fernandez-Serrano, Mercedes; Khdary, Nezar H.; Ben Mansour, Hedi (International journal of molecular sciences, 2021)
Although it is known that textile wastewater contains highly toxic contaminants whose effects in humans represent public health problems in several countries, studies involving mammal species are scarce. This study was aimed to evaluate the toxicity profile of 90-days oral administration of textile dyeing effluent (TDE) on oxidative stress status and histological changes of male mice. The TDE was collected from the textile plant of Monastir, Tunisia and evaluated for the metals, aromatic amines, and textile dyes using analytical approaches. Metal analysis by ICP-MS showed that the tested TDE exhibited very high levels of Cr, As, and Sr, which exceeded the wastewater emission limits prescribed by WHO and Tunisian authority. The screening of TDE through UPLC-MS/MS confirmed the presence of two textile dyes: a triphenylmethane dye (Crystal violet) and a disperse azo dye (Disperse yellow 3). Exposure to TDE significantly altered the malondialdehyde (MDA), Conjugated dienes (CDs), Sulfhydryl proteins (SHP) and catalase levels in the hepatic and renal tissues. Furthermore, histopathology observation showed that hepatocellular and renal lesions were induced by TDE exposure. The present study concluded that TDE may involve induction of oxidative stress which ensues in pathological lesions in several vital organs suggesting its high toxicity. Metals and textile dyes may be associated with the observed toxicological effects of the TDE. These pollutants, which may have seeped into surrounding rivers in Monastir city, can cause severe health malaise in wildlife and humans.